Participatory Rangeland Management (PRM) in Tanzania and Kenya - CGIAR Research Program on Livestock (2019)
A guideline for PRM was published by SC-USA (Flintan and Cullis 2010). PRM was then piloted in Ethiopia by NGOs with technical support from ILRI. Now being piloted in Kenya and Tanzania, adapting the approach from Ethiopia.